Early pancreaticogastrostomy: a better and novel approach for high grade traumatic pancreatic injuries - case report from tertiary care centre in India - Vyas, Shashwat; Porwal, Pankaj (International Surgery Journal, 2021)
Traumatic pancreatic injury is a rare entity which is associated with severe morbidity and mortality. The management varies according to the American association for the surgery of trauma-organ injury scale (AAST-OIS) grading of injury, hemodynamic status and time of definitive diagnosis. Non-operative versus operative management has potential risks and benefits and long term debate on the ideal management is still ongoing. A 19-year boy, with severe, generalised pain abdomen was admitted after road traffic accident. Upon admission, the investigations: ultrasonography (USG) and computed tomography (CT) scan abdomen, showed traumatic pancreatic injury (AAST-OIS, grade V), was taken for exploratory laparotomy which revealed lacerated head of pancreas along with normal distal segment of pancreas with no associated injury to nearby hollow viscera, vascular structures. He underwent primary closure of head of pancreas with distal segment pancreaticogastrostomy. Postoperatively he recovered well with no complications. In the present case, as he had traumatic pancreatic injury (AAST-OIS, grade V) and there was no involvement of hollow viscera and vascular structures, the operative intervention can decrease morbidity as by pancreaticogastrostomy we have diverted the pancreatic fluid into stomach, subsequently decreasing the chances of pseudocyst, fistula, necrosis of pancreas. Thus we conclude, high grade blunt traumatic abdomen injuries should be managed with adequate resection and subsequent reconstruction and/or drainage procedure. Pancreaticoduodenectomy, distal pancreatectomy, pancreaticogastrostomy, pancreaticojejunostomy are the available options to be used according to the grading of injury and associated injuries.